2018
DOI: 10.1186/s11556-018-0191-0
|View full text |Cite
|
Sign up to set email alerts
|

Does physical exercise improve perceptual skills and visuospatial attention in older adults? A review

Abstract: Neuroimaging studies suggest that when the brain ages, more areas are involved to perform a task in order to obtain the same results. This, together with the increase in crystalized intelligence and wisdom, is usually considered as a compensatory strategy. Research has demonstrated that physical activity might also act as a strategy and be one of the main factors that can slow down age-related perceptual and cognitive decline. Research also suggests that different types of physical exercise and sport lead to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 98 publications
(151 reference statements)
4
21
0
2
Order By: Relevance
“…Moreover, subgroup analysis according to varied types of mind‐body exercises demonstrated that only the tai chi group and the dance group had positive effects on cognitive flexibility, and other domains of executive cognition were less conclusive, suggesting that tai chi and dance mind‐body exercise were more sensitive in improving cognitive flexibility. These subgroup results were consistent with previous studies exploring dance or tai chi for their effects on executive functions in older adults …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, subgroup analysis according to varied types of mind‐body exercises demonstrated that only the tai chi group and the dance group had positive effects on cognitive flexibility, and other domains of executive cognition were less conclusive, suggesting that tai chi and dance mind‐body exercise were more sensitive in improving cognitive flexibility. These subgroup results were consistent with previous studies exploring dance or tai chi for their effects on executive functions in older adults …”
Section: Discussionsupporting
confidence: 93%
“…These subgroup results were consistent with previous studies exploring dance or tai chi for their effects on executive functions in older adults. 48,49 Language, learning, and memory are also essential factors for assessing cognitive performance. Our results suggested that mind-body exercises were beneficial for increasing the fluency of verbal language and promoting learning ability, especially tai chi, and dance exercise had an advantage in these terms.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Several studies have indicated that children and adolescent who spend more time in physical activities have better academic performance than those who are sedentary ( Ayers and Sariscsany, 2010 ). Researchers suggesting that young people may improve mental acuity, skills, and strategies through physical exercise ( Donnelly et al, 2016 ) and supports the idea that cognitive performance improves with physical exercise that makes adolescents more efficient on reaction time tasks and more flexible on attention-orientation tasks ( Muiños and Ballesteros, 2014 , 2018 ; Alesi et al, 2016 ; Zach and Shalom, 2016 ; Burns et al, 2017 ; Kashfi et al, 2019 ). Furthermore, a well-managed physical exercise may facilitate certain aspects of information processing in children and adolescent ( Tomporowski et al, 2011 ).…”
Section: Introductionmentioning
confidence: 85%
“…In this study, he participated as a special reference and was not examined using statistical analysis. Recent research has demonstrated that older martial arts athletes (judo and karate) perform better than non-athletes of the same age in the investigation of peripheral vision and perceptual asymmetry tasks (Muiños and Ballesteros, 2014 ), and physical activities including martial arts can improve peripheral vision properties in older individuals [for a review, see (Muiños and Ballesteros, 2018 )]. It was invaluable that Shihan who are awarded the eighth Dan and Hanshi title, which is the highest attainable rank in Japan (with over 40 years prior kendo experience, but acceptant rate is below 1%), participated in this study, and the data regarding his visual behavior is extremely valuable, not only for science but also in the practical domain.…”
Section: Discussionmentioning
confidence: 99%